2015
DOI: 10.1210/en.2014-2003
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin Prevents Obesity, Hepatic Steatosis, and Glucose Intolerance in Male Mice Independent of Fibroblast Growth Factor 21

Abstract: The molecular mechanisms and metabolic pathways whereby the citrus flavonoid, naringenin, reduces dyslipidemia and improves glucose tolerance were investigated in C57BL6/J wild-type mice and fibroblast growth factor 21 (FGF21) null (Fgf21(-/-)) mice. FGF21 regulates energy homeostasis and the metabolic adaptation to fasting. One avenue of this regulation is through induction of peroxisome proliferator-activated receptor-γ coactivator-1α (Pgc1a), a regulator of hepatic fatty acid oxidation and ketogenesis. Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 63 publications
(104 reference statements)
4
71
2
Order By: Relevance
“…Moreover, elevated hepatic glucose production was also observed in the same strain of FGF21 null mice in which hypoglycaemia was initially detected , and this result was corroborated by impaired glucose clearance in animals with liver‐specific FGF21 ablation . Of interest, fasting hypoglycaemia was not reported in other independently generated strains of FGF21 knockout mice . Furthermore, the in vitro activity also argues against FGF21 as a direct stimulator of gluconeogenesis; in hepatocytes, the main liver cell type targeted by FGF21 , this protein suppresses glucose output in a manner comparable to that of insulin .…”
Section: Fgf21 and Glucose Metabolismmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, elevated hepatic glucose production was also observed in the same strain of FGF21 null mice in which hypoglycaemia was initially detected , and this result was corroborated by impaired glucose clearance in animals with liver‐specific FGF21 ablation . Of interest, fasting hypoglycaemia was not reported in other independently generated strains of FGF21 knockout mice . Furthermore, the in vitro activity also argues against FGF21 as a direct stimulator of gluconeogenesis; in hepatocytes, the main liver cell type targeted by FGF21 , this protein suppresses glucose output in a manner comparable to that of insulin .…”
Section: Fgf21 and Glucose Metabolismmentioning
confidence: 88%
“…FGF21 transgenic mice were shown to be leaner than their wild‐type littermates and protected against diet‐induced obesity , but also had a proportionally higher fat mass . FGF21 knockout animals were partially lipodystrophic in one study , but obese in several others . FGF21 is a potent antihyperglycaemic agent in mice , with an FGF21 antagonist elevating glucose in vivo , yet FGF21 was reported to either induce gluconeogenesis or have no physiological relation to glucose homeostasis in animals .…”
Section: Controversies In the Fgf21 Fieldmentioning
confidence: 99%
“…Naringenin is a metabolite of naringin and this molecule reduces the plasma lipid levels in an experimental hyperlipidemia and obesity model . Moreover, Assini et al . reported that naringenin supplementation prevented high fat diet‐induced obesity in wild‐type and transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…In ovarectomized mice with metabolic disturbances, also, naringenin attenuated hepatic lipid accumulation, visceral and subcutaneous adiposity, insulin resistance, fasting glucose, and plasma total cholesterol (Ke et al, ). Lower adiposity occurred as a result of reduced caloric intake (Ke et al, ), whereas inhibition of hepatic triglyceride accumulation was exerted by decreasing expression of lipogenesis gene, Srebf1c , as well as by induction of hepatic genes involved in fatty acid oxidation, including peroxisome proliferator‐activated receptor gamma coactivator‐1 and Cpt1a (Assini et al, ).…”
Section: Treatment Of Non‐alcoholic Fatty Liver Diseasementioning
confidence: 99%